Spontaneous intracranial hypotension syndrome presented with sixth cranial nerve palsy: a case report - Sousa-Santos, Patrick Emanuell; Pozzobon, Pedro Machry; Lemos, Ana Flavia Andrade; Vieigas, Caroline; Junior, Gilberto Magioni; Alvarenga, Tarcísio Nunes; Teixeira, Igor de Lima e; Lopes, Laura Cardia (Headache Medicine, 2022)
Introduction Spontaneous intracranial hypotension (SIH) is a secondary cause of headache often misdiagnosed and underdiagnosed disorder. The main presentation is orthostatic headache. An uncommon symptom is cranial nerve palsy. We described a case of SIH that presented to our service with sixth cranial nerve palsy. Case Report Female, 39 years old, no relevant medical past or history of trauma, awoke due intense holocranial headache, associated with vomiting and photophobia, worsening in orthostasis. In the general emergency department, she was release with prescription of analgesics and topiramate, without resolution. After a week, the patient reported diplopia and was referred to our service, a tertiary center. In admission, she kept an intense orthostatic headache and in neurologic examination she presented right sixth nerve palsy, no other deficits. Laboratorial tests were normal, including metabolic and infectious marks. Cerebrospinal fluid (CSF) opening pressure was low (50 mmH2O) and analysis showed elevated protein levels (158mg/dl). MRI showed diffuse pachymeningeal enhancement and venous sinus distension, mainly in superior sagittal venous sinus. CT myelogram detected a spinal CSF leak in transition C1-C2. Initially, performed hydration and bed rest, while patient with partial improvement of headache. An epidural blood patch was then performed using 15ml of autologous blood with compatible contrast and lidocaine. There was complete resolution of pain after the procedure and four weeks later complete resolution of right sixth nerve palsy. Discussion According to International Classification of Headaches Disorders, third edition (ICHD-3), the headache attributed to SIH is descripted as a headache has developed in temporal relation to low CSF pressure (<60mm H2O) and/or evidence of CSF leakage on imaging. (To see the complete abstract, please, check out the PDF).